2002
DOI: 10.1093/jhered/93.5.331
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Structure in the European Flat Oyster (Ostrea edulis L.) as Revealed by Microsatellite Polymorphism

Abstract: Genetic differentiation of the flat oyster (Ostrea edulis) was studied along the European coast, from Norway to the Black Sea, by means of variation at five microsatellite loci. The results show a mild but significant isolation-by-distance profile, a noticeable between-sample variance in expected heterozygosity, and a tendency for Atlantic populations to be less variable than Mediterranean ones. This does not provide support for the existence of a single large panmictic population for this larvae-broadcasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
146
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(174 citation statements)
references
References 35 publications
25
146
2
1
Order By: Relevance
“…In such cases, random drift occurs locally, and genetic structure can develop in the form of isolation-by-distance. This genetic pattern has been revealed in some high dispersal marine invertebrates, such as in the European flat oyster Ostrea edulis using microsatellite loci and mtDNA sequence data (Launey et al 2002;Diaz-Almela et al 2004) and in the pelagic crustacean Megenyctiphanes norvegica (Zane et al 2000) using mtDNA data only.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In such cases, random drift occurs locally, and genetic structure can develop in the form of isolation-by-distance. This genetic pattern has been revealed in some high dispersal marine invertebrates, such as in the European flat oyster Ostrea edulis using microsatellite loci and mtDNA sequence data (Launey et al 2002;Diaz-Almela et al 2004) and in the pelagic crustacean Megenyctiphanes norvegica (Zane et al 2000) using mtDNA data only.…”
Section: Introductionmentioning
confidence: 84%
“…The role of the Atlantic-Mediterranean division as a potential barrier to gene flow has increasingly been investigated for various planktotrophic invertebrate species (e.g., Borsa et al 1997;Launey et al 2002;DiazAlmela et al 2004;Duran et al 2004a;Stamatis et al 2004Stamatis et al , 2006Saavedra and Pena 2005;Calderon et al 2008). While the Strait of Gibraltar geographically divides the two basins, the Almería-Oran front is thought to be a genetic separation area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in species dispersal are primarily determined by the ontogeny of the organisms and are partially correlated with the time that larvae spend in the plankton. However, it has been demonstrated that even in species with apparently high dispersal capability, relatively strong population structure may occur (Launey et al 2002;Zane et al 2000). Potential long-distance movements may also be hindered by the existence of other physical and historical factors acting on population's connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the AtlantoMediterranean transition, the Almeria-Oran Front (AOF) located inside the Mediterranean has been defined as the main boundary between Atlantic and Mediterranean surface waters, but the transition at the biological level still remains controversial (Borsa et al 1997;Cimmaruta et al 2005;Patarnello et al 2007) and marine species display different patterns of genetic structure at both sides of this particular area (e.g. Quesada et al 1995;Launey et al 2002;Rios et al 2002;Bargelloni et al 2003). Population genetic analyses have been applied to a scarce number of echinoderm species along the Atlantic-Mediterranean area, but the available data demonstrated different levels of gene flow between basins depending not only on the species' life history but also on the genetic markers used.…”
Section: Introductionmentioning
confidence: 99%